Heat Treatment Optimization for Nickel-based Cast Superalloy - Ancona Orozco, David (My University, 2021)
Nickel-based superalloys are broadly used in the aerospace industry for applications at elevated service temperatures. Haynes 282 is a recently developed, gamma-prime (γ ′ ) strengthened, nickel-based superalloy that can be manufactured in different ways, such as wrought methods, powder methods, and castings. An important difference between these methods is the lower mechanical performance found in the cast version of the alloy. A way to improve the mechanical properties of cast Haynes 282 is through a tailored heat treatment that considers the different properties of the material and the microstructural changes required. The objective of this thesis work was to define alternative heat treatments to improve the ductility and strength of cast Haynes 282. These proposals were based on different studies found in literature, simulations, and microstructural analysis performed at GKN Aerospace. The heat treatments were tested and compared with reference values from the standard heat treatment recommended by Haynes International, and with a standard heat treatment developed by GKN. The tensile tests were carried out at room and elevated temperature, and their results, in combination with the microstructural analysis of the secondary phases performed in the different heat treated samples, showed an improvement in mechanical properties from a couple of heat treatment proposals. A proposed heat treatment, labeled HT10, showed a potential improvement of tensile strength, ductility and containment properties at an elevated temperature of 750 °C. Haynes standard heat treatment also showed improved properties between the two temperatures, when compared to the standard GKN heat treatment.
Keywords: Nickel superalloy; Haynes 282; heat treatment; mechanical properties; microstructure; ductility; containment; cast materia; precipitation; gamma prime; carbides